The Role of Pesantren and Its Literacy Culture in Strengthening Moderate Islam in Indonesia - Ali, Ali Muhdi; Fachrizal Halim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study explores the strategic role of pesantren in promoting religious moderation through the cultivation of a literacy culture. Amid rising concerns over radicalism fueled by weak religious understanding and digital misinformation, pesantren emerges as resilient institutions fostering comprehensive Islamic learning grounded in textual literacy. The research aims to analyze the motivations behind literacy practices, the development models applied, the structural and cultural efforts by pesantren, and the contributions of students and alumnae in spreading moderate Islamic values. Through a qualitative approach and descriptive method, data were collected via observation, interviews, and document analysis at Pesantren Nurul Ummah Yogyakarta. The findings reveal five dominant literacy motivations: theological drive, kyai role modeling, academic obligations, personal interest, and economic incentives. Literacy practices are institutionalized through both individual and group habituation models. Pesantren support these initiatives structurally (e.g., through curricula and publishing bodies) and informally (e.g., by promoting mutala’ah and media engagement). The students and alumni have contributed significantly to the intellectual Islamic discourse via publications, teaching, and digital media. This study confirms that pesantren-based literacy development is pivotal to building a moderate, peaceful, and inclusive Islamic civilization in Indonesia.